55th AIAA/ASME/ASCE/AHS/ASC Structures, Structural Dynamics, and Materials Conference 2014
DOI: 10.2514/6.2014-0345
|View full text |Cite
|
Sign up to set email alerts
|

A Nonlinear Controller for Flutter Suppression: from Simulation to Wind Tunnel Testing

Abstract: Active control for flutter suppression and limit cycle oscillation of a wind tunnel wing section is presented. Unsteady aerodynamics is modelled with strip theory and the incompressible two-dimensional classical theory of Theodorsen. A good correlation of the stability behaviour between simulation and experimental data is achieved. The paper focuses on the introduction of a nonlinearity in the plunge degree of freedom of an experimental wind tunnel test rig and the design of a nonlinear controller based on par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

7
1

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 18 publications
0
15
0
Order By: Relevance
“…The coefficients of the above aeroelastic system are detailed partly in [6] and partly in the Appendix at the end of this manuscript. This allows one to setup the numerical model starting from the baseline aeroelastic parameters of the pitch-plunge aerofoil described later on.…”
Section: Unsteady Aeroelastic Numerical Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…The coefficients of the above aeroelastic system are detailed partly in [6] and partly in the Appendix at the end of this manuscript. This allows one to setup the numerical model starting from the baseline aeroelastic parameters of the pitch-plunge aerofoil described later on.…”
Section: Unsteady Aeroelastic Numerical Modelmentioning
confidence: 99%
“…Theoretical work and numerical modelling have primarily been on controlling smooth and non-smooth nonlinear aeroelastic systems by Da Ronch et al [6] and Jiffri et al [7]. More recent experimental developments include measurement of the aeroelastic system's parameters and open-loop investigations, experimental testing conducted on piezo-MFC bimorph actuation for morphing wing technology and the development and manufacture of a flexible wing for aeroelastic testing by Fichera et al [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a continuation of this work, the authors of this investigation performed partial feedback linearization for a numerical model corresponding to a low speed wind tunnel model with a nonlinearity in the plunge degree of freedom. 7 It was shown that the nonlinear controller outperforms a linear control design based on pole placement as the latter fails to achieve any significant reduction in the amplitude of the LCO. Also, optimal control has been tested for flutter suppression, for example, Huang et al 8 designed a Linear Quadratic Gaussian control that takes into account a control input delay and applied the control at an experimental wind tunnel model for flutter suppression.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a nonlinear control design methods was tested for a nonlinear experimental wind-tunnel rig for LCO suppression and was compared against conventional linear techniques . 13 Ideally though, a controller that can adapt during changes of the flow conditions such as airspeed or density is desired. Recent advances in adaptive control and especially in L 1 adaptive control theory made possible the application of adaptive controllers for the control of uncertain non linear systems.…”
mentioning
confidence: 99%